An Assessment of trace metals in selected Leafy vegetables in Lagos state - Ogunjimi, Temitope Fadekemi (Universidade Federal de Viçosa, 2023)
Man’s existence, survival and wellbeing are tied to the quality of the resources in the environment. Globally as population increases with industrial development, the resources in the environment becomes threatened due to heightened level of pollution especially in the cities. Leafy vegetables can be exposed to trace metals contamination because they are commonly grown within the urban and peri-urban areas due to their perishability. Thus, this study assessed the levels of cadmium (Cd), chromium (Cr), lead (Pb), copper (Cu), zinc (Zn) and iron (Fe) in 5 leafy vegetables’ samples of Telfairia occidentalis, Celosia argentea, Corchorus olitorius, Talinum triangulare and Vernonia amygdalina sourced from two markets in Lagos state. The metals determination was analyzed using Atomic Absorption Spectrophotometer (AAS). The daily intake of metals and the non- carcinogenic health risks through these vegetables’ consumption were calculated. Cd was not detected in all the vegetables, while Pd and Cr were only observed in T. Occidentalis (20.82 mg kg-1) and in C. olitorius (7.89 mg kg-1) from Oyingbo and Mile 12 markets respectively. Among the trace metals, Fe had the highest concentration in all the vegetables with a range between 392.66 – 2,072.97 mg kg-1 and 573.13 – 1,255.38 mg kg-1 in Mile 12 and Oyingbo markets, respectively. Zn concentration was significantly different among the vegetables in both markets with the highest concentration in C. argentea (308.33 mg kg-1), T. triangulare (303.96 mg kg-1), and lowest in C. olitorius (97.1 mg kg-1) and V. amygdalina (102.33 mg kg-1) in Mile 12 and Oyingbo market respectively. Besides, Cu had the lowest concentration ranging between 4.55 – 33.34 mg kg-1 and 0.17 – 7.34 mg kg-1. The levels of Pb, Cr, Zn and Fe were above allowable limits by FAO/WHO (1996). The daily intake of metals due to the exposure of the analyzed metal were above the permitted limit per day, except for Cu. The target hazard quotient and hazard risk index for each metal were above one (1) in all the vegetables. This indicates non- carcinogenic risks from the vegetables if consumed by humans regularly. This study suggests the need for improvement on pollution control measures and continuous monitoring of these vegetables for human’s safety. Keywords: Pollution. Trace metals. Leafy vegetables. Health risks. Markets. Lagos.

A existência, a sobrevivência e o bem-estar do homem estão ligados à qualidade dos recursos do meio ambiente. Globalmente, à medida que a população aumenta com o desenvolvimento industrial, os recursos do meio ambiente se tornam ameaçados devido ao alto nível de poluição, especialmente nas cidades. Vegetais folhosos podem ser expostos a contaminação por metais residuais porque são comumente cultivados em áreas urbanas e periurbanas devido à sua perecibilidade. Assim, este estudo avaliou os teores de cádmio (Cd), cromo (Cr), chumbo (Pb), cobre (Cu), zinco (Zn) e ferro (Fe) em amostras de 5 vegetais folhosos (Telfairia occidentalis, Celosia argentea, Corchorus olitorius, Talinum triangulare e Vernonia amygdalina) provenientes de dois mercados no estado de Lagos. A determinação dos metais foi analisada por Espectrofotômetro de Absorção Atômica (AAS). A ingestão diária de metais e os riscos não cancerígenos à saúde através do consumo desses vegetais foram calculados. Cd não foi detectado em todos os vegetais, Pd e Cr foram observados apenas em T. Occidentalis (20.82 mg kg-1) e em C. olitorius (7.89 mg kg-1) dos mercados de Oyingbo e Mile 12, respectivamente. Os demais metais apresentaram variação entre as hortaliças selecionadas em ambos os mercados, na ordem de Cu < Zn < Fe. O Zn foi significativamente diferente entre as hortaliças em ambos os mercados, sendo o mais alto em C. argentea (308.3 mg kg-1), T. triangulare (303.96 mg kg-1), e mais baixo em C.olitorus (97.1 mg kg-1), V. amygdalina (102 mg kg-1) no mercado Mile 12 e Oyingbo, respectivamente. Além disso, o Cu apresentou a menor concentração variando entre 4.55 – 33.34 mg kg-1 e 0.17 – 7.34 mg kg-1. Os níveis de Pb, Cr, Zn e Fe estavam acima dos limites permitidos pela FAO/WHO (1996). A ingestão diária de metais devido à exposição do metal analisado ficou acima do limite permitido por dia, exceto para Cu. O quociente de risco alvo e o índice de risco de xperigo para cada metal foram acima de um (1) em todos os vegetais. Isso indica riscos não cancerígenos dos vegetais se consumidos por humanos regularmente. Este estudo sugere a necessidade de melhorias nas medidas de controle da poluição e monitoramento contínuo dessas hortaliças para a segurança humana. Palavras-chave: Poluição. Metais residuais. Vegetais folhosos. Riscos de saúde. Mercados. Lagos.
Avaliação de traços de metais em vegetais folhosos no estado de Lagos
Keywords: Poluição agrícola - Lagos (Nigéria); Hortaliças - Efeito dos metais pesados; Hortaliças - Efeitos da poluição; Fisiologia Vegetal